A Medical Team’s Perspective Regarding Presence of the Family Members of Patients during Cardiopulmonary Resuscitation in the Intensive Care Unit - Mina Golestani; Ataollah Asadi Louyeh; Farzaneh Sheikholeslami; Ehsan Kazem Nezhad Leyli; Shiv Kumar (Journal of Holistic Nursing and Midwifery)
Introduction: The basic needs of a patient and his/her family members are to be supported during health care and especially during critical situations. One such support is required during cardiopulmonary resuscitation (CPR).Hence knowing the perspective of medical persons about “Family member s Presence during Resuscitation” (FPDR) in the Intensive Care Unit (ICU) is important. Methods and Materials: This research was a descriptive-analytic cross-sectional study. The population consisted of 360 members of the medical team in the ICUs of educational hospitals in Rasht during 2014–2015. Data were collected by means of census sampling using a two-part questionnaire, which included demographic information and the medical team s perspective. Fischer exact test, spearman s coefficient, logistic regression, and the Kruskal-Wallis test were used to analyze the results of the study. Results: The findings showed that 156 (43%) medical team members had experience of FPDR. Only 71 (19.7%) stated that they would invite family members to be present during the resuscitation process. The Fisher test showed a significant difference between the medical team s perspective of FPDR (P=0.033), with the majority of the emergency specialists (40%) and anesthesiology (4.2%) showing the highest and lowest agreement respectively about FPDR. The logistic regression model showed that the perspective of the medical team with a Bacheler's Degree (BS). In nursing degree (OR=4.3, p<0.021), an MSC. Nursing degree (OR=6.9, P<0.018), an anesthesiologist associate degree (OR=22.5, P<0.001), a BS. anesthesiologist degree (OR=5.7, P<0.029), and an emergency specialist status (OR=19.8, P<0.032) had a more positive attitude toward FPDR compared with the general practitioners. Conclusion: Considering the medical team s perspective of the importance of FPDR, it is necessary to formulate an instruction in ICUs to provide the grounds for it.